2019
DOI: 10.3892/mmr.2019.10537
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of icariin in experimental spinal cord injury via its antioxidant, anti‑neuroinflammatory and anti‑apoptotic properties

Abstract: icariin is a type of flavonoid derived from the chinese herbal plant Epimedium sagittatum Maxim. Mounting evidence has confirmed the beneficial effects of icariin in neurological diseases, including spinal cord injury (Sci). The aim of the present study was to investigate the neuroprotective effects of icariin in Sci and the precise underlying mechanism. The weight-drop injury technique was applied to construct an Sci model in Sprague-dawley rats. icariin (35 µmol/kg) was administered orally once daily for 7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…It demonstrates neuroprotective potential and was found to enhance memory in a model of Alzheimer's disease (AD) in mice. Furthermore, the compound has been shown to possess antioxidant [7], anti-inflammatory [8], cardioprotective [8], hepatoprotective [9], anti-osteoporotic [10], and antidepressant [11] activities. Recently, the anti-tumor activity of ICA was reviewed [12].…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrates neuroprotective potential and was found to enhance memory in a model of Alzheimer's disease (AD) in mice. Furthermore, the compound has been shown to possess antioxidant [7], anti-inflammatory [8], cardioprotective [8], hepatoprotective [9], anti-osteoporotic [10], and antidepressant [11] activities. Recently, the anti-tumor activity of ICA was reviewed [12].…”
Section: Introductionmentioning
confidence: 99%
“…IL-1b can promote SCI progression by activating the NF-kB [35]. Jia et al [36] demonstrated that icariin protected against SCI by inhibiting the levels of IL-1b, IL-6, and TNF-a. In the present study, BML-111 alleviated SCI by reversing the increase of TNF-a, IL-1b, and IL-6 in serum and spinal cord tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that these compounds may antagonize Aβ formation, scavenge free radicals, reduce inflammation, regulate mitochondrial functions and promote axonal maturation in the central nervous system [13, 18, 26, 27]. Icariin, a component extracted from Epimedium, has a beneficiary action on experimental spinal cord injury through its anti-oxidant, anti-neuroinflammatory, and anti-apoptotic role [28]. Our results showed that the active compounds could reduce the deposition of Aβ in the AD model mouse and improve the cognition including spatial and episodic memory.…”
Section: Discussionmentioning
confidence: 99%